2011
DOI: 10.1021/jf2029384
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Accumulation, Distribution, and Depletion of Furaltadone and Nifursol Residues in Poultry Muscle, Liver, and Gizzard

Abstract: Nitrofurans were broadly used as an extremely effective veterinary antibiotic especially in pig and poultry production farms. Because of fears of the carcinogenic effects on humans, the nitrofurans were banned from use in livestock production in many countries, including the European Union. The present study examines the accumulation, distribution, and depletion of furaltadone and nifursol and of their tissue-bound metabolites [3-amino-5-morpholinomethyl-2-oxazolidinone (AMOZ) and 3,5-dinitro-salicylic acid hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 8 The ENRO has a wide spectrum of activity and being widely used as veterinary drug to improve health conditions. It has good absorption and high bioavailability with good penetration into body tissues and found at high concentrations in the excretory organs, especially the liver with high withdrawal time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 8 The ENRO has a wide spectrum of activity and being widely used as veterinary drug to improve health conditions. It has good absorption and high bioavailability with good penetration into body tissues and found at high concentrations in the excretory organs, especially the liver with high withdrawal time.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The indiscriminate use of ENRO without observing their withdrawal period may create hazards for human health throughout the country. This study aims to determine the residues of ENRO at marketing age by using HPLC with UV detection in broilers and to compare it with the maximum residual limit (MRL) recommended by FAO/WHO [7] and Barbosa [8] as 100 and 200 µg/kg for meat and liver respectively, to provide a considerable data on the ENRO residues regarding the human safety.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrofuran antibiotics including furazolidone, furaltadone, nitrofurazone and nitrofurantoin are a class of synthetic broad spectrum antibiotics which have been widely used both prophylactically and therapeutically for various bacterial and protozoan infections in fish, prawn, bees, swine, cattle and poultry [1]. However, since the early 1990s, various experimental animal studies have shown that nitrofurans and their metabolites have potential mutagenicity and genotoxicity [2].…”
Section: Introductionmentioning
confidence: 99%
“…For nitrofurazone, the situation was somewhat different, showing SEM levels in liver and muscle of up to 35 and 28 µg/kg, respectively, which on a molar basis were also much higher than observed for the other drugs. Barbosa et al (2011) fed 19-week-old laying hens with feed containing either 150 mg/kg of furaltadone or 100 mg/kg of nifursol for a period of 5 weeks followed by 3 weeks on clean feed. Animals were slaughtered at the end of the treatment or after the additional 3 weeks on clean feed, and muscle, liver and gizzards were examined for the parent compound and the side-chains, the latter without prior extraction of tissues.…”
Section: Transfer To Eggsmentioning
confidence: 99%